Noise exposure to tractor drivers in field operations. Issue 4 (10th December 2019) - ,; Dewangan, K.N.; Patel, T.
Equivalent sound pressure level (Leq ) at the tractor drivers' ear level was assessed in tillage operations. Measurements were performed on six models of tractors attached with five different tillage implements namely mould board plough, disc plough, rotavator, disk harrow and duck foot cultivator and operated at three different forward speeds. Noise exposure to the drivers was compared with the permissible exposure limits (PELs) in OSHA (1983) and NIOSH (1998). The results showed that noise intensity at the drivers' ear level varied between 91.7 and 97.5 dB(A). Increase in tractor forward speed increased noise intensity. Noise exposure was considerably higher with rotavator as compared with other tillage implements, while noise exposure was comparable in other tillage implements. Noise exposure to the tractors drivers exceeded the PELs for 8 h operation. According to PELs in OSHA and NIOSH, the tractors should be operated nearly 2 and 7 h, respectively.